2014
DOI: 10.1002/smll.201302990
|View full text |Cite
|
Sign up to set email alerts
|

CMOS‐Compatible Silicon Nanowire Field‐Effect Transistors for Ultrasensitive and Label‐Free MicroRNAs Sensing

Abstract: MicroRNAs (miRNAs) have been regarded as promising biomarkers for the diagnosis and prognosis of early-stage cancer as their expression levels are associated with different types of human cancers. However, it is a challenge to produce low-cost miRNA sensors, as well as retain a high sensitivity, both of which are essential factors that must be considered in fabricating nanoscale biosensors and in future biomedical applications. To address such challenges, we develop a complementary metal oxide semiconductor (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 44 publications
(51 reference statements)
0
75
0
4
Order By: Relevance
“…As shown in Table 1, several studies have used NWFET-based biosensors for label-free, ultra-high-sensitivity, and real-time detection of various biological targets, including a single virus 2 , adenosine triphosphate and kinase binding 3 , neuronal signals 4 , metal ions 5,6 , bacterial toxins 7 , dopamine 8 , DNA [9][10][11] , RNA 12,13 , enzyme and cancer biomarkers [14][15][16][17][18][19] , human hormones 20 , and cytokines 21,22 . These studies have demonstrated that NWFET-based biosensors represent a powerful detection platform for a broad range of biological and chemical species in a solution.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, several studies have used NWFET-based biosensors for label-free, ultra-high-sensitivity, and real-time detection of various biological targets, including a single virus 2 , adenosine triphosphate and kinase binding 3 , neuronal signals 4 , metal ions 5,6 , bacterial toxins 7 , dopamine 8 , DNA [9][10][11] , RNA 12,13 , enzyme and cancer biomarkers [14][15][16][17][18][19] , human hormones 20 , and cytokines 21,22 . These studies have demonstrated that NWFET-based biosensors represent a powerful detection platform for a broad range of biological and chemical species in a solution.…”
Section: Introductionmentioning
confidence: 99%
“…The developed assay allowed for the detection of miRNA levels down to 1 zeptomole (ca. 600 copies) in one minute (Lu et al, 2014). Table 2 summarizes the analytical performance of potentiometric, conductometric, impedimetric, and field-effect transistor-based biosensors currently employed for miRNA analysis.…”
Section: Field-effect Transistor-based Biosensorsmentioning
confidence: 99%
“…An enhanced signalto-noise ratio (SNR; SNR > 20 for 1 fM DNA) was obtained, implying a detection floor of 50 aM. Next, they used this DNA-modified CMOS-compatible FET biosensor to measure miRNA molecules (Lu et al 2014). The nanosensor showed a rapid response of miR-21 and miR-205, with a low limit of detection of 1 zmol, and an excellent discrimination of single-nucleotide mismatched sequences.…”
Section: Dna-dna/rna Hybridizationsmentioning
confidence: 99%